Biodegradation behavior of bacterial cellulose fiber reinforces with starch/chitosan biocomposite - Farisah, Abdul Aziz (2010)
Biocomposite from starch, bacterial cellulose and chitosan offer A good mechanical properties. The objectiveS of this study are to produce bacterial cellulose fiber reinforce with starch/chitosan biocomposite and to study the characterization of the biocomposite on mechanical, chemical and also biodegradation behavior. The research conducted with 4 samples with difference composition of chitosan (0.5%, 1%, 1.5% and 2% w/w) and 4 samples with difference composition of bacterial cellulose (0%, 7%, 14% and 21% ). The bacterial cellulose film produced by Acetobacter Xylinum was blend and mixED with chitosan and starch. The film will be analyzed by using Universal Testing Machine, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), Gas Pynometer, Swelling absorption and soil burial degradation method. Among the four samples, the films with 21% of bacterial cellulose, 6% starch and 2% of chitosan composition showed a good mechanical property. It was supported by FTIR results where the tapioca starch, chitosan and bacterial cellulose were in compatible by composition and inter-molecular chemical bonds such as existed in the sample. Moreover, the SEM analysis showed a smooth and homogenous structure of the film. Besides, Gas Pynometer analysis showed the average density more than 1 for the entire sample. The absorption of water was increased proportionate with the composition of bacterial cellulose and chitosan in swelling absorption. The soil burial test indicated the increased degradation rate as the chitosan and bacterial cellulose content was increased. As a conclusion, the film fabricated had a potential application in future to be used as packaging material because as it had good mechanical properties and biodegradable can protect the environment.